Development and characterization of (1-x)BiYO3-xBiMnO3 ceramics for Ferro-photovoltaic applications - Prajapati P.; Singh A.K. (My University, 2025)
The rare combination of ferroelectricity, low band gap and high carrier mobility in a material can facilitate exceptional photovoltaic efficiency. In this paper, we attempted to reduce the band gap and improve the conductivity of ferroelectric solid solution BiY(1-x)MnxO3 by varying composition. The BiY(1-x)MnxO3 (x = 0.0, 0.10, 0.25, 0.50, 0.75) samples were prepared by high energy ball milling method and structural, dielectric, optical, electrical and ferroelectric properties were analyzed systematically. Herein, we show that band gap of the material is drastically reduced from 3.0 eV (BiYO3) to 1.76 eV (x = 0.50) and the samples exhibit ferroelectric behavior with significant polarization. Compound resistance of grain and grain boundaries were also found to reduce with increase in Mn concentration in the BiY(1-x)MnxO3 solid solution, demonstrating improvement in semiconducting behaviour of the material. Thus, solid solution formation of BiMnO3 with BiYO3, tunes band gap in useful region, improves electrical conduction and enhances ferroelectric polarization showing good potential for high performance solar cell and thermoelectric applications. © 2022 Elsevier Ltd and Techna Group S.r.l.